Relationship between diverticulosis and nonalcoholic fatty liver disease in elderly patients - Sahin, Abdurrahman; Tunc, Nurettin; Demirel, Ulvi; Poyrazoglu, Orhan Kursat; Yalniz, Mehmet; Bahcecioglu, Ibrahim Halil (Sage Publications Ltd, 2018)
Objective To compare clinical and laboratory features of elderly patients with and without diverticulosis and assess factors related to hepatosteatosis. Method This retrospective case-control study analysed the clinical and laboratory data, colonoscopy and abdominal ultrasonography records of patients >65 years who underwent colonoscopies. Subjects were categorized according to the presence and absence of colonic diverticulosis. Univariate/multivariate logistic regression analyses were performed to evaluate the independent predictive factors of hepatosteatosis. Results A total of 355 patients were enrolled in the study: 169 had colonic diverticulosis; and 186 without colonic diverticulosis formed the control group. Age, sex and chronic disorders associated with the metabolic syndrome did not differ between the diverticulosis and control groups. The rate of hepatosteatosis was lower in patients with diverticulosis compared with the control group (27% versus 42%, respectively). Diabetes mellitus, hyperlipidaemia and hepatosteatosis were more common among patients aged <75 years. In the multivariate logistic regression analysis, diverticulosis remained an independent predictor of hepatosteatosis (odds ratio 0.529; 95% confidence interval 0.323, 0.866). Other independent predictive factors in the multivariate analysis were triglyceride and albumin. Conclusion Diverticulosis in the elderly was found to be a negative predictor of hepatosteatosis. Higher values of albumin and triglyceride in conjunction with the absence of diverticulosis may be suggestive of nonalcoholic fatty liver disease in the elderly.
Keywords: Diverticulosis; hepatosteatosis; undernutrition